Radiation damage monitoring in Hadron Forward calorimetry - Zöğ, İrem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Placed at high absolute pseudorapidity, Hadron Forward (HF) calorimeters are exposed to high energy particles more than other parts of the CMS HCAL detector in CERN. Radiation resulting from high energy particles lead to a decrease in trans parency of the HF quartz ﬁbres, eﬀecting the calibration and decreasing the lifetime of the calorimeter. Thus, observation of change in transparency of the HF quartz ﬁbres with respect to the accumulated dose of radiation and time is crucial. From the ﬁrst proposal in 2003 to 2018, radiation damage (RadDam) tests and measurements have been performed with the HCAL Laser System. Yet, the HCAL Laser generates wide pulses, resulting in signals spread over several time slices and are hard to analyse. A new light source that is specialized for the HF RadDam system has been proposed as part of the Phase I Upgrade of the HF calorimeter. In this thesis, the analysis of HF Online RadDam Measurements with the new specialized light source is described. Noisy events are eliminated using time-to-digital converter (TDC) information from the new electronic chips QIE10. No signiﬁcant diﬀerence in radiation damage is ob served in channels at a given pseudorapidity for varying azimuthal angle. The closer the channels are to the beam line, the more pronounced radiation damage and recovery become. Total systematic error is estimated as 0.5%.
Keywords: Hadron interactions.; Particles (Nuclear physics)